(untitled) (Journal of Engineering, 2020)
In this paper, three types of epoxy-based coatings (Polyamide, pure Polyamine, and Polyamine reinforced by glass-flake) used as a lining for potable water tanks were studied using experimental and finite element methods. Tensile, impact, and fatigue tests were conducted on uncoated and coated AISI 316 stainless steel. The test results show that the applied epoxy based coating improves the mechanical properties, increases of fatigue crack resistance, and enhance the dynamic fracture toughness. The fatigue crack propagation is influenced by the compositions of epoxy coating, and the glass-flake improves the coating resistance to fatigue crack propagation compared to other types.